LRP-1 Binds Fibrinogen in a Sialylation-Dependent Manner A Quartz Crystal Microbalance Study - Gao, Daniel L (Langmuir : the ACS journal of surfaces and colloids, 2023)
Cardiovascular disease (CVD) is the leading cause of mortality in the United States. Atherosclerosis, the dominant condition leading to CVD, is characterized by fibrofatty plaque formation. Fibrinogen, an important clotting factor, has been known to promote atherogenesis as it retains the ability to trigger smooth muscle cell proliferation, localize in areas crucial to plaque progression, and bind both platelets and leukocytes. Yet, these consequences can be suppressed through anti-inflammatory receptors like LRP-1─an endocytic receptor part of the LDLR family responsible for the endocytosis of cell debris and protein degradation products. However, the continual progression of atherosclerosis in many patients indicates that such clearance mechanisms, deemed efferocytosis, are impaired during atherosclerosis. Using the quartz crystal microbalance with dissipation monitoring (QCM-D) as a platform to investigate receptor-ligand interactions, we identify fibrinogen to be a ligand of LRP-1 and characterize its binding with LRP-1. By examining a key player in atherosclerosis development─the effect of sialidase on receptor efficacy─we found that the desialylation of LRP-1 reduces its ability to bind fibrinogen. Protein docking simulations highlighted the N-terminus portion of fibrinogen's α domain as the LRP-1 docking site. The sialylated O-linked glycans at T894 and T935 have the potential to mediate direct binding of LRP-1 to fibrinogen and support the tertiary structure of LRP-1. These phenomena are important in showing a probable cause of defective efferocytosis that occurs readily during atherosclerosis